Synthesizing evidence to guide the design and implementation of effective strategies for discontinuing postoperative antibiotic prophylaxis in surgical settings: an umbrella review post-WHO 2018 recommendations - George Msema Bwire; Renatus B. Magati; Hafidhi H. Ntissi; Tusaligwe Mbilinyi; Martine A. Manguzu; Goodluck G. Nyondo; Belinda J. Njiro; Lilian B. Nkinda; Castory G. Munishi; Obadia Nyongole; Pacifique Ndayishimiye; Mtebe V. Majigo (Systematic Reviews)
Abstract Background Postoperative antibiotic prophylaxis (PAP) involves using antibiotics after surgery to prevent surgical site infections (SSIs). However, studies have shown that PAP offers no additional benefits compared to discontinuation after surgical incision closure, prompting its de-implementation to prevent unnecessary antibiotic use that may contribute to antibiotic resistance. We conducted this review to synthesize evidence for guiding the design and implementation of effective strategies for discontinuing PAP practice and optimizing antibiotic use in surgical settings. Methods This umbrella review searched for articles from PubMed/MEDLINE and Scopus, focusing on reviews conducted on human subjects on PAP to prevent SSIs, published in English language from 2019 to 5th July 2024. This review followed guidelines from PRISMA-P and PRIOR. The risk of bias (methodological quality) was assessed using AMSTAR-2. The pooled risk ratio (RR) was estimated using a fixed-effects model (Mantel–Haenszel method), while I 2 was used to assess the heterogeneity between reviews. This review was registered with PROSPERO (CRD42024566124). Results In our umbrella review, we screened 1156 articles, with 28 review articles found eligible for final analysis, involving over 457 primary studies. About 80,483 patients were involved in 9 meta-analysis reviews, which were used to estimate the pooled RR. We found no significant benefits to patients from continuing PAP beyond 24-h post-surgery compared to immediate discontinuation, RR: 1.07 (95% CI: 0.97–1.17, I 2: 25%, p-value: 0.22). Strategies such as regularly assessing and refining guidelines to fit specific surgical settings and patients’ characteristics, multidisciplinary collaboration, availability of resources needed for best practices, education and training healthcare workers on SSI prevention and antibiotic stewardship, and patient education in SSI prevention and proper antibiotic use were recommended to improve best practices in surgical settings. Conclusions Prolonging antibiotic prophylaxis beyond 24-h post-surgery did not show significant protective benefits against SSIs. Our findings support the 2018 WHO recommendation for the immediate discontinuation of PAP following surgical incision closure in clean and clean-contaminated procedures. Further de-implementation research studies are needed to guide the effective discontinuation of PAP practice.